Cultivating Digital Reflexivity as Resistance to Digital Dualism: Doing Digital Ethnography with U.S. Congregations During the covid-19 Pandemic - Raffety, Erin (Ecclesial practices, 2023)
This article reflexively reviews methods for training researchers developed during a national studying of thriving congregations in the United States during the covid-19 pandemic (2020-2022) as a case study on doing digital ethnography (ethnography that uses digital methods to study and engage critically with digital culture). The article outlines the importance of digital culture (expressions of identity offline are not separate from online formation; see Campbell 2012) and digital dualism (outmoded assumptions about binaries between online/offline spaces; see Jurgenson 2011) for doing digital ethnography, and argues that as long as digital dualism lurks not only among congregations, but also within researchers and their methodologies, it undermines knowledge of congregations. Therefore, the article develops the concept of digital reflexivity (the interrogation of one’s own digital cultural experiences, identities, and power, in tension with one’s relationships), arguing for its usefulness for ethnographic studies of congregations, practices of congregational ministry, and theological education.